Moral and ethical values ​​in responsible citizen education: a systematic review - Gamarra Chirinos, Olga Patricia; Gamarra Carrasco, Ana Janette; Vergara Vásquez, Anibal Teobaldo; Villanueva Javez, Jesús Antonio (Revista del CLAD Reforma y Democracia, 2025)
UNESCO promotes education for global citizenship, highlighting the interconnection between citizenship training and the development of individuals. Currently, the need arises to transform society through democracy, active participation and multiculturalism through education. The objective of this research is to delve into the need for responsible citizen training from the rescue of moral and ethical values ​​in society. This research is based on a positivist, descriptive and documentary paradigm, in which the PRISMA 2020 method is applied. A total of 39 articles were screened taking into account Google Academic, Dialnet and Redalyc as academic search engines in three categories a) moral values ; b) ethical values; and c) responsible citizen training, developed in Spanish-speaking countries. As results, it was obtained that responsible citizen training is related to the rescue of both moral and ethical values ​​that in turn promote human rights and the rules of coexistence for the construction of responsible and integral citizens. It is considered essential that curricular changes be implemented in higher education that strengthen critical participation and coexistence adapted to the diverse social realities and for future generations.
Keywords: Citizenship training; Values; Ethical values; Moral values; Responsibility; Citizenship; Citizenship education